Roles of Biomolecules in the Biosynthesis of Silver Nanoparticles：Case of Gardenia jasminoides Extract - 吕芬芬 高艺 黄加乐 孙道华 李清彪 (Chinese journal of chemical engineering, 2014)
Rapid development of biosynthesis of metal nanoparticles using plants has attracted extensive interests to further investigate this novel and eco-friendly method. In the biosynthesis process, the plant may act as reducing agent, capping agent or shape directing agent. However, identifying specific roles of various components in the plant is challenging. In this study, we use biosynthesis of silver nanoparticles with Gardenia jasminoides Ellis ex-tract to address this issue. The formation process of silver nanoparticles is investigated and the nanoparticles are characterized with the ultraviolet-visible spectroscopy, Fourier transform infrared spectra and scanning electron mi-croscopy. The results indicate that the Gardenia jasminoides Ellis extract can reduce silver ions to form silver nanoparticles, stabilize the nanoparticles, and affect the growth of silver nanocrystal to form silver nanowires. Only geniposide in the extract exhibits good shape-directing ability for silver nanowires. It is found that bovine albumin is a potential capping agent, whereas rutin, gallic acid and chlorogenic acid possess reducing and capping ability.